'Starting with a Prayer': Women, Faith, and Security in Fiji. Issue 1 (March 2015) - George, Nicole; Taylor, John P.; Morgain, Rachel
Abstract Scholars of global security have recently been captured by the idea that there is a link between 'sex and world peace'. They argue that the security of states and the international system should be understood as conditional upon the social, economic, and political standing of women. Accordingly, they contend that societies and states that display chauvinistic and discriminatory sociocultural influences are more tolerant of high levels of gender disadvantage and violence towards women, and more likely to be marked by general levels of belligerence, violence, and insecurity. Ideologies of faith are identified as helping to fuel this scenario. Hence, proponents of the 'sex and world peace' thesis construct a strongly oppositional relationship between gender and faith on the one hand, and gender and security on the other. In this paper, I challenge the idea that efforts to build security, gendered or otherwise, are only effective if they are secularised. I draw on examples from the Pacific Islands to defend my case. While I concede that faith can be a source of insecurity in many parts of the Pacific Islands region, and is often invoked in ways that legitimise violence, I also discuss important examples that illustrate where and how faith is a resource for the region's women peacebuilders who have resisted violence in interpersonal, intercommunal, and interregional contexts.